Pengaruh Brand Image,Product Knowledge, dan Perceived Quality Terhadap Purchase Intention Produk Hanasui Mattedorable Lip Cream: Studi pada Masyarakat di Kabupaten Kebumen - Kulsumaningtyas, Sheny; Wiwoho, Gunarso (LP3M Universitas Putra Bangsa, 2023)
This study aims to determine the effect of Brand Image, Product Knowledge, and Perceived Quality on Purchase Intentions for the Hanasui Mattedorable Lip Cream product (studi8es in communities in Kebumen Regency). This research was conducted by taking a sample of 100 respondents, especially women who are in the Kebumen Regency area. The population in this study are people in Kebumen Regency who know the Hanasui Mattedorable Lip Cream product and intend to buy the product. The data used in this study is primary data obtained from the answers of respondents collected through questionnaires. The research method used is non-probability sampling with purposive sampling technique. Hypothesis testing was carried out using multiple linear regression analysis techniques using SPSS for windows version 22.0. The results of this study indicate that the variable Brand Image partially has no significant effect on Purchase Intentions. Meanwhile, the variables of Product Knowledge and Perceived Quality partially influence Purchase Intentions for the Hanasui Mattedorable Lip Cream product. Brand Image, Product Knowledge, and Perceived Quality together have a significant effect on Purchase Intentions for Hanasui Mattedorable Lip Cream products.